Subhaloes gone Notts: the clustering properties of subhaloes. Issue 4 (24th January 2014) - Pujol, Arnau; Gaztañaga, Enrique; Giocoli, Carlo; Knebe, Alexander; Pearce, Frazer R.; Skibba, Ramin A.; Ascasibar, Yago; Behroozi, Peter; Elahi, Pascal; Han, Jiaxin; Lux, Hanni; Muldrew, Stuart I.; et al.
Abstract: We present a study of the substructure finder dependence of subhalo clustering in the Aquarius Simulation. We run 11 different subhalo finders on the haloes of the Aquarius Simulation and study their differences in the density profile, mass fraction and two-point correlation function of subhaloes in haloes. We also study the mass and v max dependence of subhalo clustering. As the Aquarius Simulation has been run at different resolutions, we study the convergence with higher resolutions. We find that the agreement between finders is at around the 10 per cent level inside R 200 and at intermediate resolutions when a mass threshold is applied, and better than 5 per cent when v max is restricted instead of mass. However, some discrepancies appear in the highest resolution, underlined by an observed resolution dependence of subhalo clustering. This dependence is stronger for the smallest subhaloes, which are more clustered in the highest resolution, due to the detection of subhaloes within subhaloes (the sub-subhalo term). This effect modifies the mass dependence of clustering in the highest resolutions. We discuss implications of our results for models of subhalo clustering and their relation with galaxy clustering.